Functional assessment of vitamin D status by a novel metabolic approach: the low vitamin D profile concept - Herrmann, Markus; Zelzer, Sieglinde; Cavalier, Etienne; Kleber, Marcus E.; Drexler-Helmberg, Camilla; Schlenke, Peter; Curcic, Pero; Keppel, Martin H; Enko, Dietmar; Scharnagl, Hubert; Pilz, Stefan; März, Winfried (Clinical chemistry, 2023)
Abstract - Background - Determining serum 25-hydroxyvitamin D [25(OH)D], 24,25-dihydroxyvitamin D [24,25(OH)2D] and the vitamin D metabolite ratio (VMR) allows the identification of individuals with a low vitamin D metabolite profile. Here, we evaluated if such a functional approach provides superior diagnostic information to serum 25(OH)D alone. - Methods - 25(OH)D, 24,25(OH)2D, and the VMR were determined in participants of the DESIRE (Desirable Vitamin D Concentrations, n = 2010) and the LURIC (Ludwigshafen Risk and Cardiovascular Health, n = 2456) studies. A low vitamin D metabolite profile (vitamin D insufficiency) was defined by a 24,25(OH)2D concentration <1.2 ng/mL (<3 nmol/L) and a VMR <4%. Parathyroid hormone (PTH) and bone turnover markers were measured in both cohorts, whereas 10-year mortality data was recorded in LURIC only. - Results - The median age in DESIRE and LURIC was 43.3 and 63.8 years, respectively. Median 25(OH)D concentrations were 27.2 ng/mL (68.0 nmol/L) and 15.5 ng/mL (38.8 nmol/L), respectively. Serum 25(OH)D deficiency, defined as <20.2 ng/mL (<50 nmol/L), was present in 483 (24.0%) and 1701 (69.3%) participants of DESIRE and LURIC, respectively. In contrast, only 77 (3.8%) and 521 (21.2%) participants had a low vitamin D metabolite profile. Regardless of the serum 25(OH)D concentration, a low vitamin D metabolite profile was associated with a significantly higher PTH, accelerated bone metabolism, and higher all-cause mortality than an unremarkable vitamin D metabolite profile. - Conclusions - The personalized assessment of vitamin D status using a functional approach better identifies patients with accelerated bone metabolism and increased mortality than the use of a fixed 25(OH)D cutoff of 20 ng/mL (50 nmol/L).